2014
DOI: 10.1108/jpif-08-2013-0050
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of economic factors on REITs' capital structure around the world

Abstract: Purpose – This paper aims to examine the determinants of the capital structure of real estate investment trusts (REITs) across the world and explore whether this structure is characterized by any common factors. Design/methodology/approach – Endogenous and exogenous factors that affect the financial management of real estate firms are identified in the analysis. “Regular” (static) panel data regression analysis, as well as dynamic panel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…This shows that the food processing industry is able to generate returns from operations. Similarly, the firm size is also positively associated with firm value, and this is in line with the studies of Rovolis and Feidakis (2014). Further, the association of tangibility and firm value is positive and significant at the one percent level of significance, and this supports the agency cost theory, and is in support to the studies of Rajan and Zingales (1995) and Tripathy and Pradhan (2014).…”
Section: Resultssupporting
confidence: 84%
“…This shows that the food processing industry is able to generate returns from operations. Similarly, the firm size is also positively associated with firm value, and this is in line with the studies of Rovolis and Feidakis (2014). Further, the association of tangibility and firm value is positive and significant at the one percent level of significance, and this supports the agency cost theory, and is in support to the studies of Rajan and Zingales (1995) and Tripathy and Pradhan (2014).…”
Section: Resultssupporting
confidence: 84%
“…Yunus (2012) also found a cointegration between real estate market and key macroeconomic factors but concluded a shock to inflation would result in a positive response in real estate return while a shock to interest rates provides a negative real estate return response. The study was supported by Rovolis and Feidakis (2014). Goebel et al (2013) reported REIT possessing similarities with non-equity REIT in terms of return and found a great influence of interest rates on REIT returns.…”
Section: Discussion Of Findingsmentioning
confidence: 62%
“…9. Rovolis and Feidakis (2014) analyze 334 REITs from 20 countries between 2005 and 2010 and find the determinants of REIT capital structure are similar to the predictions of corporate finance theories. Dogan et al (2019) further investigate country-specific factors and find that institutional differences such as leverage restrictions and payout requirements also influence use of leverage.…”
Section: Notesmentioning
confidence: 73%